Enhanced Federal Collaborations in Implementation Science and Research of HIV Prevention and Treatment. (1st July 2022) - Purcell, David W.; Namkung Lee, Ann; Dempsey, Antigone; Gordon, Christopher
Abstract: Over the past decade, national initiatives in the United States (U.S.) have focused HIV prevention and care programs and research to optimize the delivery of HIV prevention and treatment through implementation research. Although existing biomedical and behavioral prevention tools could end HIV in the U.S., the implementation of these tools has been uneven because of many factors, including organizational capacity, insufficient uptake by key populations, lack of success with prioritizing by geography or population growth, and inadequate scaling. To address these challenges, the federal government has funded programs, research, and evaluation projects aimed at improving health outcomes among people with HIV and people vulnerable to HIV acquisition. Increasingly, several special federal efforts are being conducted under the umbrella of "implementation science and research" that are essential components to scaling up evidence-based HIV prevention and treatment interventions in the U.S. This paper describes federal collaborations that have supported this increased focus on implementation from the perspective of 3 agencies in the U.S. Department of Health and Human Services; the Centers for Disease Control and Prevention, the National Institutes of Health, and the Health Resources and Services Administration. These federal collaborations have resulted in improved communication and coordination of efforts in the shaping and alignment of priorities in research and service delivery, increased implementation research conducted in real-world community and clinical settings and provided a feedback loop to expedite action in response to emerging evidence from such projects.